Pemanfaatan Instagram Sebagai Sarana Pemasaran Produk Secara Digital Untuk Para Santri Majelis Ta’lim Faizul Haq - Tri Santoso; Ardian Dwi Praba; Adelia Alviyana; Sulistianto SW (CV. Multi Kreasi Media, 2023)
Advances in technology make all processes easier. Technology can also be an alternative or replace existing conventional processes. This technological advancement can affect anyone and anywhere in different fields. One of the areas that can be influenced by technology is the field of marketing and one of the parties that can be influenced is the students in the Faizul Haq Ta'lim Assembly. So far, the students have focused on studying religion, but they do not yet have an understanding of marketing concepts, especially using technology. With the help of technology, they can market their own products or promote the activities of the assembly where they studied. Seeing this problem, this community service activity was carried out in order to increase the skills of the students of the Faizul Haq Ta'lim Assembly in terms of marketing the products they produce through the help of Instagram social media. Then the method of community service carried out is planning, preparation and evaluation. The techniques used in it are the explanation of the theory contained in the modules that have been distributed and practice on how to use the Instagram application as well as questions and answers about the material provided. This community service is carried out online using the zoom application and other supporting applications such as Instagram, Google Chrome, WhatsApp. In addition, this service uses pretest and posttest questionnaires to find out the results of this community service that has been carried out.